Force feedback control for bilateral teleoperation system with unknown Prandtl-Ishlinskii hysteresis. Issue 13 (September 2020) - Hua, Changchun; Wang, Yilu; Yang, Yana; Guan, Xinping
Abstract: Hysteresis nonlinearity is a common phenomenon in mechanical actuators. Specially, it appears when the direction of motion of mechanical actuated joint is reversed in robotic manipulator. This paper focuses on the force feedback control problem for bilateral teleoperation system with unknown Prandtl-Ishlinskii (PI) hysteresis. First, an improved sliding mode observer with adaptive gains is provided for estimating the external force signals acting on the manipulators. This removes the need for force sensors and reduces hardware-cost. Next, to improve transparency and guarantee the passivity of the communication network, a four-channel wave variable transformation scheme including force information is introduced. Then, an adaptive switching-based control framework is proposed to deal with Prandtl-Ishlinskii hysteresis dynamics. Finally, the theoretical findings are supported by simulation and experiment results.